Addressing graduate student mental health - Albrecht, Opal (Kansas State University, 2014)
It is estimated that nearly twenty-five percent of graduate students experience symptoms of depression, anxiety, or seasonal affective disorder (Kernan, Bogart, & Wheat, 2011). Graduate students are defined as being unique, vulnerable, and at risk for experiencing a variety of challenges (Hyun, Quinn, Madon, & Lustig, 2006). Several of these challenges can result in high levels of stress (Oswalt & Riddock, 2007). Failing to cope with this stress can lead to increased stress levels, more severe mental health concerns or illness, and potentially dropping out (Hamaideh, 2011). Graduate students are not completing programs at the rate that they should, in fact attrition rates are estimated to be as high as fifty percent for some graduate programs (Kent, 2013). Understanding the effect mental health has on a student’s ability to persist through a graduate program is crucial to understanding the graduate student experience. It is suggested that higher education institutions begin to acknowledge the stress graduate students endure, the transitional struggles they encounter, and the barriers graduate students overcome to seek help. Based on the literature and personal experience, it is proposed that higher education institutions focus on preventative measures when combating the mental health challenges graduate students experience. This report provides a summary of the best strategies to consider when focusing on graduate student mental health. These strategies include the creation of an office devoted to providing graduate students with the support services they deserve.
Keywords: Mental health; Graduate students; Mental illness; Stress; Higher education; Higher Education (0745); Psychology (0621)